The protozooplankton in the region south of the mouth of the Santa Cruz channel – Itamaracá – PE – Brazil - Costa, Alejandro Esteweson Santos Faustino; Silva, Andréa Pinto; Silva, Tâmara de Almeida e; Nascimento-Vieira, Dilma Aguiar do; Neumann-Leitão, Sigrid (Revista Nordestina de Zoologia, 2013)
In 1994 some studies were realized south of the mouth of the Santa Cruz channel, Itamaracá (PE), in order to obtain information about processes of importation and exportation of organic matter from the mangroves. In one of these studies, samples were collected in three sites, every three hours during a period of 24 hrs, in the dry and rainy season. A total of 20 taxa was identified. A significant difference was found between both seasons. The tintinnids were dominant in the dry season, while the forams in the rainy season. The most conspicuous species in the dry season were Leprotintinnus nordqvisti and Favella ehrenbergii; they occurred in all the samples and accounted for about 80% of the whole protozooplanktonic community in some cases. In the rainy season the forams were very important; Quinqueloculina sp. and some unidentified forams were sometimes responsible for about 50% of the community. Two groups of samples and species were revealed by the cluster analysis; one typically of the rainy season, and other typically of the dry season.